Students’ orientation to the past, present, future and its dependence on their way of self-affirmation - Yevchenko, Iryna M.; Masliuk, Andrii M.; Podolyak, Nataliia M.; Girchenko, Olena L. (Linguistics and Culture Review, 2021)
For a person to realize their self-improvement, they need to develop their self-affirmation and social communication the function of which consists in the aspiration of a person to recognition, self-realization, and achievement of role and personality certainty. Due to the importance of this issue, the authors aimed to determine the relationship of self-affirmation strategies with the time perspective of the personality. The study of the profile of the students’ time perspective was conducted. It was determined to be close to the optimal ones. Significant correlation was established between the indicators of self-repression strategy and the orientation towards the future. During the study, it was proved that orientation to the negative past is typical of the students with a strategy of self-suppression, constructive self-affirmation strategy coreelates with turning to the positive past. Students with a dominant type of self-affirmation are the most oriented to the future.